2000
DOI: 10.2337/diabetes.49.8.1281
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of AMP-activated protein kinase activation and glucose transport in contracting slow-twitch muscle.

Abstract: 5AMP-activated protein kinase (AMPK) has been suggested to be a key regulatory protein in exercise signaling of muscle glucose transport. To test this hypothesis, we investigated whether muscle glycogen levels affect AMPK activation and glucose transport stimulation similarly during contractions. Rats were preconditioned by a combination of swimming exercise and diet to obtain a glycogen-supercompensated group (high muscle glycogen content [HG]) with ~3-fold higher muscle glycogen levels than a glycogen-deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
152
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 36 publications
17
152
1
1
Order By: Relevance
“…Altogether, the present study suggests that during exercise, covalent regulation of ␣ 2 -AMPK on Thr 172 is glycogen dependent, but that ACC␤ Ser 221 phosphorylation does not parallel ␣ 2 -AMPK activity when circulating glucose and epinephrine levels are standardized. This is supported by findings in isolated contracting rodent skeletal muscle with high and low muscle glycogen levels, where differences in ␣ 2 -AMPK activity did not translate into differences in ACC activity (8).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Altogether, the present study suggests that during exercise, covalent regulation of ␣ 2 -AMPK on Thr 172 is glycogen dependent, but that ACC␤ Ser 221 phosphorylation does not parallel ␣ 2 -AMPK activity when circulating glucose and epinephrine levels are standardized. This is supported by findings in isolated contracting rodent skeletal muscle with high and low muscle glycogen levels, where differences in ␣ 2 -AMPK activity did not translate into differences in ACC activity (8).…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, circulating epinephrine did not differ significantly between conditions, and, still, ␣ 2 -AMPK activity during exercise was markedly higher in L-CHO than in H-CHO (Table 1). This suggests that altered muscle glycogen alone can influence ␣ 2 -AMPK activity in human skeletal muscle during exercise independently of adrenergic stimulation, in agreement with studies in rodent muscle (8). On this basis, AMPK could be a likely candidate mediating the effect of muscle glycogen on fat oxidation through regulation of ACC activity and malonylCoA formation, as suggested earlier (34,41).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Insulin action was assessed 24 h after AICAR administration, long after its acute effects on plasma glucose and glycerol levels had dissipated. Also, ACC activity, which is considered a good indicator of AMPK activation (48), was similar in liver of HF-Con and HF-AIC groups during the clamp, suggesting that the effect of AICAR on AMPK activation had worn off by 24 h. Finally, in a separate study, we found no residual increase in AMPK or reduction in ACC activity in muscle or liver of control rats 24 h after injection of a similar dose of AICAR (A.S. and N.B.R., unpublished observations). Whether by activating AMPK a single dose of AICAR induced chronic changes (e.g., at the level of transcription [49]) that inhibited hepatic glucose output or enhanced glucose utilization was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that AMPK activity in skeletal muscle is increased following exercise in both humans and rodents [4][5][6][7][8]. Furthermore, activation of AMPK in resting skeletal muscle increases both glucose uptake and fatty acid oxidation [9] as well as gene expression [10; 11], leading to speculation that AMPK could mediate the increase in these pathways in response to exercise {Winder, 1999 3011 /id format ref}.…”
Section: Introductionmentioning
confidence: 99%